2017
DOI: 10.1353/hpu.2017.0039
|View full text |Cite
|
Sign up to set email alerts
|

Rural African Americans’ Perspectives on Mental Health: Comparing Focus Groups and Deliberative Democracy Forums

Abstract: A number of approaches have been used to obtain community members' health perspectives. Health services researchers often conduct focus groups while political scientists and community groups may hold forums. To compare and contrast these two approaches, we conducted six focus groups (n = 50) and seven deliberative democracy forums (n = 233) to obtain the perspectives of rural African Americans on mental health problems in their community. Inductive qualitative analysis found three common themes: rural African … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 30 publications
0
6
1
Order By: Relevance
“…Our first major finding was that young White women and middle-aged White men experienced higher rates of psychological distress compared to all other race, age, and gender groups. This finding is contrary to the long-standing, consistent findings on psychological distress, which have reported higher rates of psychological distress among African Americans when compared to Whites [ 7 , 8 , 11 , 25 , 39 ]. Despite the plethora of studies supporting this notion, other studies have found that under certain conditions, some Whites experience poorer mental health than Black Americans.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Our first major finding was that young White women and middle-aged White men experienced higher rates of psychological distress compared to all other race, age, and gender groups. This finding is contrary to the long-standing, consistent findings on psychological distress, which have reported higher rates of psychological distress among African Americans when compared to Whites [ 7 , 8 , 11 , 25 , 39 ]. Despite the plethora of studies supporting this notion, other studies have found that under certain conditions, some Whites experience poorer mental health than Black Americans.…”
Section: Discussioncontrasting
confidence: 99%
“…These concerns exist for a range of mental health questionnaires, such as the highly structured, lay interviewer-administered World Health Organization Composite International Diagnostic Interview (WHO-CIDI) and the semi-structured, clinician-administered World Mental Health Structured Clinical Interview for the Diagnostic and Statistical Manual of Mental Disorders ((DSM), WMH SCID 2000), which are both tied to DSM criteria. For example, previous studies have examined issues such as interviewer and gender bias in making clinical decisions about African Americans [ 1 ]; the operationalization of DSM depression criteria in the CIDI and SCID [ 2 , 3 ]; mental health stigma [ 4 , 5 ]; and mental health literacy among African Americans [ 6 , 7 ]. In the past, these issues have made it difficult for African Americans to report depression symptoms, especially to interviewers and clinicians who are not African American.…”
Section: Introductionmentioning
confidence: 99%
“…These study participants confirmed that communal values contributed to avoiding acknowledging MH problems. Additionally, Haynes et al (2017) and Sullivan et al (2017) both found that community members have deep insights into the MH needs and barriers. These MH advocates offered insights consonant with those studies.…”
Section: Discussionmentioning
confidence: 99%
“…Previous literature has found that DD methods provide more authentic public opinions ( 11 ). Moreover, DD may be particularly useful when considering policies and programs for marginalized populations ( 11 , 12 ).…”
Section: Introductionmentioning
confidence: 99%